Hotspot DNMT3A mutations in clonal hematopoiesis and acute myeloid leukemia sensitize cells to azacytidine via viral mimicry response - Scheller, Marina; Ludwig, Anne Kathrin; Göllner, Stefanie; Rohde, Christian; Krämer, Stephen; Stäble, Sina; Janssen, Maike; Müller, James-Arne; He, Lixiazi; Bäumer, Nicole; Arnold, Christian; Gerß, Joachim; et al. (Nature cancer, 2021)
Somatic mutations in DNA methyltransferase 3A (DNMT3A) are among the most frequent alterations in clonal hematopoiesis (CH) and acute myeloid leukemia (AML), with a hotspot in exon 23 at arginine 882 (DNMT3AR882). Here, we demonstrate that DNMT3AR882H-dependent CH and AML cells are specifically susceptible to the hypomethylating agent azacytidine (AZA). Addition of AZA to chemotherapy prolonged AML survival solely in individuals with DNMT3AR882 mutations, suggesting its potential as a predictive marker for AZA response. AML and CH mouse models confirmed AZA susceptibility specifically in DNMT3AR882H-expressing cells. Hematopoietic stem cells (HSCs) and progenitor cells expressing DNMT3AR882H exhibited cell autonomous viral mimicry response as a result of focal DNA hypomethylation at retrotransposon sequences. Administration of AZA boosted hypomethylation of retrotransposons specifically in DNMT3AR882H-expressing cells and maintained elevated levels of canonical interferon-stimulated genes (ISGs), thus leading to suppressed protein translation and increased apoptosis.